The Anti-inflammatory Potential of Selected Plant-derived Compounds in Respiratory Diseases - Wieczfinska, Joanna; Sitarek, Przemyslaw; Kowalczyk, Tomasz; Skała, Ewa; Pawliczak, Rafal (Current Pharmaceutical Design, 2020)
Inflammation plays a major role in chronic airway diseases like asthma, COPD, and cystic fibrosis. Inflammation plays a crucial role in the worsening of the lung function resulting in worsening symptoms. The inflammatory process is very complexed, therefore the strategies for developing an effective treatment for inflammatory airway diseases would benefit from the use of natural substances. Plant products have demonstrated anti-inflammatory properties on various lung disease models and numerous natural plant agents have successfully been used to treat inflammation. Naturally occurring substances may exert some anti-inflammatory effects by modulating some of the inflammatory pathways. These agents have been used in different cultures for thousands of years and have proven to be relatively safe. Parthenolide, apocynin, proanthocyanidins, and boswellic acid present different mechanisms of actions - among others, through NF-ΚB or NADPH oxidase inhibition, therefore showing a wide range of applications in various inflammatory diseases. Moreover, some of them have also antioxidant properties. This review provides an overview of the anti-inflammatory effects of some of the natural agents and illustrates their great potential as sources of drugs to cover an extensive range of pharmacological effects.
Keywords: airway disease